2015
DOI: 10.47125/jesam/2015_2/01
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Habits and Distribution of Some Fish Species in the Pansipit River-Lake Taal Connection, Luzon Island, Philippines

Abstract: The interface between lakes and their outlet rivers is an interesting research site for fish community dynamics because it is immediately exposed to disturbances in lake ecosystems. In this paper, observations on the species composition, dietary habits and distribution of fish in the upstream area of Pansipit River - sole outlet of Lake Taal, were presented. Fish samples comprised of juvenile fish from 12 species, including four that were introduced. These non-native species were more abundant tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…This fish is widely distributed in shallow coastal waters in tropical and subtropical regions (Martin and Blabber, 1984), and is regarded as a predominant carnivore that feeds on planktonic crustaceans in coastal food webs (Martin and Blaber, 1983). It has also been reported that in Lake Taal, this species preys not only on copepods and cladocerans but also on chironomid larvae (Ariyaratne et al, 2008;Mendoza et al, 2015). Dinoflagellates are the main prey item for most copepod and cladoceran species (Persson and Vrede, 2006), while the chironomids rely heavily on MOB (Eller et al, 2005;Jones et al, 2008).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This fish is widely distributed in shallow coastal waters in tropical and subtropical regions (Martin and Blabber, 1984), and is regarded as a predominant carnivore that feeds on planktonic crustaceans in coastal food webs (Martin and Blaber, 1983). It has also been reported that in Lake Taal, this species preys not only on copepods and cladocerans but also on chironomid larvae (Ariyaratne et al, 2008;Mendoza et al, 2015). Dinoflagellates are the main prey item for most copepod and cladoceran species (Persson and Vrede, 2006), while the chironomids rely heavily on MOB (Eller et al, 2005;Jones et al, 2008).…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, O. niloticus is well known to have a wider range of food items, such as phytoplankton, zooplankton, insects, and fish larva. It has also been reported to undergo temporal shifts in food habits in accordance to its ontogeny and food availability (Zenebe et al, 1998;Nijiru et al, 2004;Rumisha and Nehemia, 2013;Mendoza et al, 2015). Such omnivory and food habit flexibility may be a cause of the dissociation with specific basal food sources.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies revealed that due to the limited availability of the prey item in the habitat or the phenomenon of ontogeny (George et al, 2013). According to the study of dietary habits of some fish species in the Pansipit River in Lake Taal, Luzon, Philippines, the fish Glossogobius giuris undergo various ontogenic diet shifts (Mendoza et al, 2015). The study reported that during the ontogeny of the fish, they often change their diet because of morphological changes to utilize sequentially series of prey ranging from small to much larger prey (Bejer, 2015).…”
Section: Figurementioning
confidence: 99%